SYSTEMATIC LITERATURE REVIEW : PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KECAKAPAN HIDUP YANG BERSIFAT GENERIK (SOFT SKILL) - Mufidah, Lina -; Rachmawati, Eka; Sulistyani, titik (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2023)
The purpose of the systematic literature review is to determine the effect of project-based learning on life skills (communication, responsibility, cooperation and emotional). The research method uses systematic literature review. The inclusion criteria in this study are research methods using quantitative methods, research that makes project-based learning methods on students' problems generic life skills (soft skills) students as the main study, research. The research subjects studied are elementary, junior high, high school, and student students, Research published by national publishers who have been ISSN or have been accredited by SINTA, Published year between 2019-2023, Language used Indonesian or English. The search database was conducted from October to November 2023, researchers searched literature using three databases, namely Google Scholar, and ScienceDirect. The data used in this study are secondary data obtained through data extraction from previous studies. The search found 14 journals that had been selected based on predetermined inclusion criteri. The results of the systematic literature review, namely learning using the project-based learning method, have an influence on life skills generically, including increasing communication skills, increasing student cooperation, increasing student responsibility and improving students' emotional management abilities. This character will support the independent curriculum with the main characteristics of this curriculum that support learning recovery according to learning outcomes